PENGARUH PENGENDALIAN INTERNAL DAN MORALITAS INDIVIDU TERHADAP KECENDERUNGAN FRAUD PENGELOLAAN DANA DISTRIBUTOR PT. ANDALAS MITRA PRESTASI UNIT SUNGAI PENUH - Dori HP Putra (LP2M Universitas Bina Bangsa, 2024)
This study aims to determine the influence of internal control and individual morality on the tendency of fraud in managing funds of PT. Andalas Mitra Prestasi Unit Sungai Penuh, and to determine the influence of internal control and individual morality together affect the tendency of fraud in the management of funds Distributor PT. Andalas Mitra Prestasi Unit Sungai Penuh. The result of the study is that from the results of the partial test (Test t) shows that the internal control variable does not affect the tendency of fraud in the management of funds of PT. Andalas Mitra Prestasi Unit Sungai Penuh, individual morality variables affect the tendency of fraud in managing funds Distributor PT. Andalas Mitra Prestasi Unit Sungai Penuh. The results of the simultaneous test study (Test F), show that the variables of internal control and individual morality together affect the tendency of fraud in the management of funds of PT. Andalas Mitra Prestasi Unit Sungai Full